WORKSHOP PEMBUATAN SABUN CUCI RAMAH LINGKUNGAN DARI BAHAN DASAR ECO ENZYME DI MALAKA SARI - Viana Meilani Prasetio; Komara Mulya; Eva Jeniar Noverisa; Dewi Salsabilla; Marsha Karimah Munaf; Fajar Setya Fahcriansyah; Eunike Felicia; Hifzy Aldiansyah Herdya Putra; Shafiranisa Putri Gunawan; Mario Alvianko; Mohammad Rizki Andika; Alif Putra Nur Zara (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract Eco Enzyme is the results from the fermentation process of the organic food waste (fruit and vegetable residue) combined with glucose (brown sugar, palm sugar, cane sugar) and water. Eco Enzyme can be utilized as the environmentally friendly liquid soap raw material. Japanese Language Education Department Language and Art in cooperation with North Jakarta Eco Enzyme Nusantara community organized a workshop about making liquid soap using Eco Enzyme as one of the materials. The community service activity was conducted in Malaka Sari sub-district, East Jakarta. This workshop can be highly advantageous for the communities as this community service activity’s main purpose is to increase the public awareness regarding environment and waste recycling process through Eco Enzyme liquid soap. The final product of the workshop can be utilize as detergent and phenol replacement. in addition, the final product can be sold. As the main result of making Eco Enzyme liquid soap, the communities were contributing in keeping the earth and environment. Abstrak Eco Enzyme adalah hasil fermentasi limbah dapur organik (ampas buah dan sayuran) yang dicampurkan dengan gula (gula coklat, gula merah, atau gula tebu) dan air. Eco Enzyme dapat dimanfaatkan menjadi sabun cair yang ramah lingkungan. Prodi Pendidikan Bahasa Jepang bekerjasama dengan tim dari Eco Enzyme Nusantara Cabang Jakarta Utara dalam membuat workshop mengenai pembuatan sabun cair dari eco enzyme, yang dilakukan di kelurahan Malaka Sari. hasil dari kegiatan ini adalah bertambahnya wawasan masyarakat mengenai lingkungan dan proses daur ulang sampah melalui sabun yang terbuat dari eco enzyme. Hasil yang telah dibuat dapat bermanfaat untuk membersihkan lantai dan kamar mandi, mencuci baju, mencuci piring, dan lainnya. Selain itu, sabun dari eco enzyme juga dapat dijual, sehingga bisa menambah pendapatan. Dengan membuat sabun cair dari eco enzyme, kita berpartisipasi untuk menjaga bumi dan lingkungan sekitar kita.